ANALISIS EFEKTIVITAS PEMBUKAAN REKENING ONLINE VIA MUAMALAT DIN - Lidya Agustin; Novera Martilova (CV. Adiba Aisha Amira, 2024)
This research was motivated by fluctuations in the percentage increase in the number of customers opening online accounts through Muamalat Din at PT Bank Muamalat Indonesia KC Payakumbuh, because this is new and not many people know about it. This research aims to determine and analyze the procedure for opening an online account via Muamalat Din and the effectiveness of opening an online account via Muamalat Din at Bank Muamalat Indonesia KC Payakumbuh. The research that the author conducted was a qualitative approach method, the data sources that the author took were primary data and secondary data. And data collection techniques using interviews and documentation. Meanwhile, the data analysis techniques obtained use data analysis, namely data reduction, data presentation, drawing conclusions and verification. Based on the results of the research and analysis carried out by the author, it can be concluded that opening an online account via Muamalat DIN can be said to be effective. This is because opening this account can make it easier for people who want to have an account at Bank Muamalat Indonesia KC Payakumbuh. Then it also makes it easier for people to carry out transactions anytime and anywhere comfortably. The level of effectiveness of opening an account can be seen from the indicators of accuracy of program targets, program outreach, achievement of program objectives, and program monitoring.